2022
DOI: 10.3390/su14053045
|View full text |Cite
|
Sign up to set email alerts
|

What Drives a Future German Bioeconomy? A Narrative and STEEPLE Analysis for Explorative Characterisation of Scenario Drivers

Abstract: A future bioeconomy pursues the transformation of the resource base from fossil to renewable materials in an effort to develop a holistic, sustainable production and provision system. While the significance of this change in the German context is not yet entirely explored, scenarios analysing possible pathways could support the understanding of these changes and their systemic implications. Bioeconomy in detail depends on respective framework conditions, such as the availability of biomass or technological res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Due to the current lack of momentum and the small number of players and plants in the new fields of the bioeconomy, there is little valid data available for material applications. In addition, the regional system boundary is also a simplification of reality, as biomass can be exchanged across regions (to a certain extent), which is why there is no 1:1 relationship between regionally available biomass and processing technologies (Szarka et al, 2021;Richter et al, 2022). However, there are also important ecological reasons in favour of using as much of the regionally available residual and waste materials as possible locally in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the current lack of momentum and the small number of players and plants in the new fields of the bioeconomy, there is little valid data available for material applications. In addition, the regional system boundary is also a simplification of reality, as biomass can be exchanged across regions (to a certain extent), which is why there is no 1:1 relationship between regionally available biomass and processing technologies (Szarka et al, 2021;Richter et al, 2022). However, there are also important ecological reasons in favour of using as much of the regionally available residual and waste materials as possible locally in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Farm to Fork Strategy aims to promote environmentally friendly food consumption as well as healthy food for all and to reduce food waste. Authors analysing the restrictions on chemical inputs set out in the Farm to Fork Strategy have suggested that it contributes to improving the environmental sustainability of agricultural production [118,119]. However, it has had a negative impact on socioeconomic aspects, particularly now that the war in Ukraine is increasing food supply and security problems worldwide [118].…”
Section: Discussion and Policy Implications Considering The Opportuni...mentioning
confidence: 99%
“…However, it has had a negative impact on socioeconomic aspects, particularly now that the war in Ukraine is increasing food supply and security problems worldwide [118]. Purnhagen et al [118] and Richter et al [119] showed that the increase in organic farming could also reduce food security due to the lower yields on organic farms. Therefore, biotechnological innovations and farm modernisation are particularly important for the implementation of this Strategy [89].…”
Section: Discussion and Policy Implications Considering The Opportuni...mentioning
confidence: 99%
“…The biological revolution refers to the transformative changes brought about by advancements in biological sciences, biotechnology, and the understanding of living systems. It encompasses various fields such as genomics, synthetic biology, bioengineering, and agricultural biotechnology [Richter et al 2022]. The biological revolution has significant implications for the bioeconomy.…”
Section: Introductionmentioning
confidence: 99%